Biomechanical effects of an injury prevention program in preadolescent female soccer athletes - Thompson, J. A.; Tran, A. A.; Gatewood, C. T.; Shultz, R.; Slider, A.; Delp, S. L.; Dragoo, J. L. (The American Journal of Sports Medicine, 2017)
Background: Anterior cruciate ligament (ACL) injuries are common, and children as young as 10 years of age exhibit movement patterns associated with an ACL injury risk. Prevention programs have been shown to reduce injury rates, but the mechanisms behind these programs are largely unknown. Few studies have investigated biomechanical changes after injury prevention programs in children. Purpose/Hypothesis: To investigate the effects of the F-MARC 11+ injury prevention warm-up program on changes to biomechanical risk factors for an ACL injury in preadolescent female soccer players. We hypothesized that the primary ACL injury risk factor of peak knee valgus moment would improve after training. In addition, we explored other kinematic and kinetic variables associated with ACL injuries. Study Design: Controlled laboratory study. Methods: A total of 51 female athletes aged 10 to 12 years were recruited from soccer clubs and were placed into an intervention group (n = 28; mean [±SD] age, 11.8 ± 0.8 years) and a control group (n = 23; mean age, 11.2 ± 0.6 years). The intervention group participated in 15 in-season sessions of the F-MARC 11+ program (2 times/wk). Pre- and postseason motion capture data were collected during preplanned cutting, unanticipated cutting, double-leg jump, and single-leg jump tasks. Lower extremity joint angles and moments were estimated using OpenSim, a biomechanical modeling system. Results: Athletes in the intervention group reduced their peak knee valgus moment compared with the control group during the double-leg jump (mean [±standard error of the mean] pre- to posttest change, -0.57 ± 0.27 %BW×HT vs 0.25 ± 0.25 %BW×HT, respectively; P = .034). No significant differences in the change in peak knee valgus moment were found between the groups for any other activity; however, the intervention group displayed a significant pre- to posttest increase in peak knee valgus moment during unanticipated cutting (P = .044). Additional analyses revealed an improvement in peak ankle eversion moment after training during preplanned cutting (P = .015), unanticipated cutting (P = .004), and the double-leg jump (P = .016) compared with the control group. Other secondary risk factors did not significantly improve after training, although the peak knee valgus angle improved in the control group compared with the intervention group during unanticipated cutting (P = .018). Conclusion: The F-MARC 11+ program may be effective in improving some risk factors for an ACL injury during a double-leg jump in preadolescent athletes, most notably by reducing peak knee valgus moment. Clinical Relevance: